PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN DI NISKARA COFFEE - Ade Kurniawan Siregar; Salman Paludi (Human Capital Development, 2025)
This study aims to determine the effect of service quality, product quality, and price perception on customer satisfaction at Niskara Coffee. The method used is a quantitative method. This survey was conducted by distributing questionnaires to 100 respondents using a proportional random sampling technique. This technique is used by selecting a selected population so that the entire population has an equal opportunity to be included as a sample frame. Data analysis was carried out using multiple linear analysis assisted by IBM SPSS 26. Based on the results of this study, it is known that partially each variable, namely service quality, product quality, and price perception, has a positive and significant influence on customer satisfaction. In addition, when analyzed together, the three variables are also proven to have a significant and positive influence on the level of customer satisfaction.